2023
DOI: 10.3746/pnf.2023.28.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Supplementation on Biochemical Markers of Women with Polycystic Ovarian Syndrome: A Systematic Review

Abstract: Polycystic ovary syndrome (PCOS) is a widespread endocrine disorder among fertile women and may be induced by nutritional deficiencies. In this study, we assess the impact of selenium supplementation (SS) on biochemical markers in women with PCOS. To gather relevant literature, we searched the Web of Science, Cochrane Library, Scopus, Embase, and MEDLINE databases from inception up to July 24, 2022. Subsequently, we included all published full-text randomized clinical trials examining the effects of SS versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Studies have shown that women with PCOS often have low levels of minerals, including Se. Se supplementation has been found to improve reproductive outcomes and reduce in ammatory markers by suppressing proin ammatory cytokines, as well as reactive oxygen and nitrogen species [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that women with PCOS often have low levels of minerals, including Se. Se supplementation has been found to improve reproductive outcomes and reduce in ammatory markers by suppressing proin ammatory cytokines, as well as reactive oxygen and nitrogen species [10][11][12].…”
Section: Introductionmentioning
confidence: 99%